Evaluation of commercially available DNA extraction kits for the analysis of the broiler chicken cecal microbiota. Issue 8 (27th March 2019) - Pankoke, Helga; Maus, Irena; Loh, Gunnar; Hüser, Andrea; Seifert, Jana; Tilker, Alexandra; Hark, Sarah; Sczyrba, Alexander; Pelzer, Stefan; Kleinbölting, Jessica
ABSTRACT: 16S rRNA gene amplicon sequencing is a state of the art technology to analyze bacterial communities via microbiome profiling. Choosing an appropriate DNA extraction protocol is crucial for characterizing the microbial community and can be challenging, especially when preliminary knowledge about the sample matrix is scarce. The aim of the present study was to evaluate seven commercial DNA extraction kits suitable for 16S rRNA gene amplicon sequencing of the bacterial community of the chicken cecum, taking into account different criteria such as high technical reproducibility, high bacterial diversity and easy handling. The DNA extraction kits differed strongly with respect to extractable DNA quantity, DNA quality, technical reproducibility and bacterial diversity determined after 16S rRNA gene amplicon sequencing and subsequent bioinformatic and biostatistical data processing. While some of the DNA extraction protocols under-represented specific bacterial community members, the removal of PCR inhibitors supported technical reproducibility and subsequently enhanced the recovered bacterial diversity from the chicken cecum community. In conclusion, the removal of PCR inhibitors from the sample matrix seemed to be one of the main drivers for a consistent representation of the bacterial community even of low abundant taxa in chicken cecum samples. Abstract : An accurate description of the broiler caecal microbiota is a challenging tasks starting from a suitable DNA extraction to get insights into this complex habitat that affects animal health.